2020
DOI: 10.31289/jite.v4i1.3658
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Augmented Reality for Earth Layer Structure on Android Based as a Learning Media

Abstract: Implementation of Augmented Reality for Earth Layer Structure on Android Based as A Learning Media isa research that aims to help in presenting material to Elementary School children. The research methodchosen in the completion of this study uses the 4D method (Define, Design, Develop and Disseminate) witha data collecting method using Technology Acceptance Model (TAM) built one construct with threedimensions of user assessment level of technology acceptance to support the basis of questionnaire design.AR desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…According to (Nugroho & Pramono, 2017) media is a tool of all forms which has the aim of facilitating the process of delivering information. (Deli, 2020;Putra, 2013) argues that the use of learning media that is applied to the learning process can increase students' interest in following the material presented by the teacher. (Mauludin et al, 2017) revealed that learning media that can motivate students in the implementation of learning is by utilizing learning media that are suitable for students' needs for learning materials and can encourage students to learn so that the learning outcomes obtained can increase.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Nugroho & Pramono, 2017) media is a tool of all forms which has the aim of facilitating the process of delivering information. (Deli, 2020;Putra, 2013) argues that the use of learning media that is applied to the learning process can increase students' interest in following the material presented by the teacher. (Mauludin et al, 2017) revealed that learning media that can motivate students in the implementation of learning is by utilizing learning media that are suitable for students' needs for learning materials and can encourage students to learn so that the learning outcomes obtained can increase.…”
Section: Introductionmentioning
confidence: 99%
“…Namun, hal ini masih banyak terjadi pada kalangan masyarakat tertentu yang belum begitu memahami bagaimana cara penggunaan teknologi yang sudah begitu banyak melintasi dunia khususnya di Indonesia atau pada daerah Kepulauan Riau. Pemandangan seperti ini yang menjadi perhatian khusus karena perkembangan zaman yang sudah begitu maju, maka dari itu perlu sekali pembelajaran khusus terkait dengan bagaimana cara penggunaan kemajuan teknologi dapat dipahami secara komprehensif oleh masyarakat yang mengetahui perkembangan tersebut [3].…”
unclassified